Generation of disc-like plasma from laser-matter interaction in the presence of a strong external magnetic field. (13th June 2017) - Ivanov, V V; Maximov, A V; Betti, R; Wiewior, P P; Hakel, P; Sherrill, M E
Abstract: Dynamics of laser produced plasma in a strong magnetic field was studied using a 1 MA pulsed power generator coupled to an intense, high-energy laser. A 2–2.5 MG magnetic field was generated on the surface of a rod load 0.8–1.2 mm in diameter. A sub-nanosecond laser pulse with intensity of 3 × 10 15 W cm −2 was focused on the rod load surface. Side-on laser diagnostics showed the generation of two collimated jets 1–3 mm long on the front and rear sides of the load. End-on laser diagnostics reveal that the laser produced plasma in the MG magnetic field takes the form of a thin disc as the plasma propagates along the magnetic field lines. The disc-like plasma expands radially across the magnetic field with a velocity of 250 km s −1 . An electron temperature of 400 eV was measured in the laser-produced plasma on the rod load.